Nanosilver toxicity in gills of a neotropical fish: Metal accumulation, oxidative stress, histopathology and other physiological effects - Ale, Analía (2018)
The widespread and increasing use of silver nanoparticles (AgNP) as biocide results in an unknown release into the aquatic environment. In order to contribute to the understanding of their potential toxicity, the aim of this study was to analyze branchial multiple biomarkers on the neotropical fish Prochilodus lineatus. We exposed fish to sublethal AgNP concentrations: 0 (control), 2.5 and 25.0 µg L−1. After 5 and 15 days, we analyzed in gills total Ag accumulation, oxidative stress markers (antioxidant enzymes, lipid peroxidation and antioxidant capacity against peroxyl radicals), aspartate and alanine aminotransferases activities (ALT, AST) and histopathologies (morphometric analysis, proportion of the secondary lamellae available for gas exchange, reaction indexes, and organ index -Igills-) that included mucus cell count (MCc). The Ag accumulation after 15 days was five times higher than after 5 days in the case of 25.0 μg AgNP L−1-exposure. Regarding oxidative stress, all enzymes activities were inhibited after 5 days at both AgNP concentrations. ALT activity decreased and a reduction in the antioxidant capacity was evidenced after 2.5 µg AgNP L−1 and 15 days. LPO levels and AST activity increased after the highest time of exposure and AgNP concentration, and the same occurred with Igills. MCc increased after 15 days at both AgNP concentrations. The results confirmed that the presence of low AgNP concentrations, in short and subchronic exposures, generates alterations in stress biomarkers and in the structure of this vital organ that are the gills.